ISLAM DAN PENGARUHNYA TERHADAP PERADABAN MELAYU - Herlina Herlina (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2014)
Abstract  Islam, the civilization of any kinds are becoming (manifestation) of faith and righteous deeds of man in devotion to God Almighty. Islamic civilization in enforcing not only looking at one side of the life of the world with a rich culture to advance the achievement of civilization, but also pay attention to the principle of the pursuit of happiness, by providing a way of teaching moral and civil life which in view of the diversity of the world. In the formation and development of Islamic civilization, it can not be separated from the foundations of the Islamic civilization instructions, namely: first, the Qur'an and the Sunnah, the second, the Islamic community and the third, Opener road to the other party. In addition, the Islamic civilization has certain characteristics, traits and characteristics, which different from other civilizations. These characteristics, namely universality, monotheism, balanced and moderate, and a touch of character. With these characteristics of Islamic civilization, it can be accepted in various parts of the world. Finally, this article will explain the process of entry and spread of Islamic civilization to the Malay World, which is through the process of trade, marriage, politics and others. The arrival of Islam to the nature and role of Islamic civilization will provide a very significant influence on the development and advancement of the Malay world both in the field of Aqeedah, Law, government, economy, language and literature, art and architecture, and so on.  Keywords: Islamic Civilization, Islamic influence, Malay Islamic Civilization